2021
DOI: 10.3389/fpsyg.2021.628993
|View full text |Cite
|
Sign up to set email alerts
|

What Intervention Techniques Are Effective in Changing Positive Affective Variables and Physical Activity? A Systematic Review and Meta-Analysis

Abstract: A recent meta-analysis has demonstrated that positive affective variables (PAVs) partially mediate physical activity (PA) interventions. However, the effectiveness of each intervention technique on PAVs and PA is still unknown. Thus, this meta-analytic review included two primary objectives: (1) to summarize intervention effects on PA and PAVs; (2) to examine each behavior change technique's effectiveness in modifying PAVs and PA. Following PRISMA protocols, we had searched five electronic databases by April 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…There is evidence to suggest that techniques such as providing information on the consequences of the behaviour, providing instruction on how to engage in the behaviour, and reinforcing the effort towards the behaviour, can facilitate the development of a person's confidence to be active [87]. Furthermore, a recent review has highlighted how techniques such as social comparison might promote positive affect for PA by eliciting comparisons with others [88], in the context of the current study,…”
Section: Practical Implicationsmentioning
confidence: 82%
See 1 more Smart Citation
“…There is evidence to suggest that techniques such as providing information on the consequences of the behaviour, providing instruction on how to engage in the behaviour, and reinforcing the effort towards the behaviour, can facilitate the development of a person's confidence to be active [87]. Furthermore, a recent review has highlighted how techniques such as social comparison might promote positive affect for PA by eliciting comparisons with others [88], in the context of the current study,…”
Section: Practical Implicationsmentioning
confidence: 82%
“…There is evidence to suggest that techniques such as providing information on the consequences of the behaviour, providing instruction on how to engage in the behaviour, and reinforcing the effort towards the behaviour, can facilitate the development of a person’s confidence to be active [ 87 ]. Furthermore, a recent review has highlighted how techniques such as social comparison might promote positive affect for PA by eliciting comparisons with others [ 88 ], in the context of the current study, perhaps by mothers comparing their PA alongside that of their daughters. There were considerable social complexities evident in how mothers engaged in supportive behaviours (TDF: social influences) ranging from their engagement with their daughters regarding PA, to how they utilised their social network to cultivate positive relationships with other mothers.…”
Section: Discussionmentioning
confidence: 99%
“…We based the intervention on facilitators of positive affective responses to exercise (Wienke and Jekauc, 2016), but still it is possible that the intervention content was not sufficiently relevant for changes in affect. It is possible that the focus of such an intervention should have been task-oriented teaching styles (Klos et al, 2020) or other affect-based intervention techniques (Chen et al, 2021). In this context, it seems important for future studies to examine which techniques are most effective in manipulating affective constructs -and whether these techniques are also most beneficial for habit formation (see also question 13 of the 21 questions to guide future research by Gardner et al, 2021).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…There are several approaches on how to manipulate affectbased constructs through interventions (for an overview see Conner et al, 2020;Chen et al, 2021). With regards to the potential content of interventions targeting affective responses, the qualitative study of Wienke and Jekauc (2016) identified four facilitators of positive affective responses in exercise, namely perceived competence, perceived social interaction, novelty experience, and perceived physical exertion.…”
Section: Introductionmentioning
confidence: 99%